ESTUARINE CROCODILE IN SUNGAI LIKAU - Ruhana, Hassan (UNIMAS Publisher, 2025)
Crocodile density in SNP was 1.14 without hatchlings per km. Crocodiles of different sizes could be seen in the river during the survey, suggesting that a healthy crocodile population in the river. Continuous monitoring should be carried out, as one of the mitigation measures to ensure the safety of humans, crocodiles and turtles.